The Accuracy of Trade Classification Rules: Evidence from Nasdaq - Ellis, Katrina; Michaely, Roni; O'Hara, Maureen (Journal of Financial and Quantitative Analysis, 2000)
Katrina Ellis, Roni Michaely, Maureen O'Hara, The Accuracy of Trade Classification Rules: Evidence from Nasdaq, The Journal of Financial and Quantitative Analysis, Vol. 35, No. 4 (Dec., 2000), pp. 529-551